2013
DOI: 10.1089/omi.2013.0030
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid Improves Root Antioxidant Defense System and Total Antioxidant Capacities of Flax Subjected to Cadmium

Abstract: Cadmium (Cd) disrupts the normal growth and development of plants, depending on their tolerance to this toxic element. The present study was focused on the impacts of exogenous salicylic acid (SA) on the response and regulation of the antioxidant defense system and membrane lipids to 16-day-old flax plantlets under Cd stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 66 publications
3
16
0
Order By: Relevance
“…Belkadhi et al reported that the Cd-treated plantlets presoaked with SA exhibited less lipid and protein oxidation and membrane alteration, as well as a high level of total antioxidant capacities and increased activities of antioxidant enzymes except of CAT. They suggested that SA plays an important role in triggering the root antioxidant system, thereby preventing membrane damage as well as the denaturation of its components [57]. In this study, we found that in SA-treated plants, POD activity was increased in all treatment groups but CAT activity was decreased on the 10 th day (Tables 1 and 4).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Belkadhi et al reported that the Cd-treated plantlets presoaked with SA exhibited less lipid and protein oxidation and membrane alteration, as well as a high level of total antioxidant capacities and increased activities of antioxidant enzymes except of CAT. They suggested that SA plays an important role in triggering the root antioxidant system, thereby preventing membrane damage as well as the denaturation of its components [57]. In this study, we found that in SA-treated plants, POD activity was increased in all treatment groups but CAT activity was decreased on the 10 th day (Tables 1 and 4).…”
Section: Discussionsupporting
confidence: 54%
“…At the same time, since adaptation to oxidative stress includes not only the regulation of the synthesis and repair of proteins but also increased andioxidant activity [60]. Belkadhi et al reported that antioxidant activity effect was improved by SA in Cd-stressed plantlets [57].…”
Section: Discussionmentioning
confidence: 99%
“…Belkadhi et al (2013) showed that exogenous SA protected membranes against a loss of integrity and lipid peroxidation by increasing fatty acid unsaturation in Linum usitatissimum roots. Later, Belkadhi et al 2015 further reported that exogenous SA also protected phospholipids of L. usitatissimum by decreasing the percentages of monogalactosyldiacylglycerol, phosphatidylcholine, phosphatidylethanolamine and phosphatidylglycerol.…”
Section: Salicylic Acid (Sa)mentioning
confidence: 99%
“…It has been reported that exogenous SA treatment may ameliorate the damaging effects of heavy metals in many plants (Agami and Mohamed 2013;Dražic and Mihailovic 2005;Krantev et al 2008;Metwally et al 2003;Popova et al 2009). SA-induced Cd tolerance in plants is attributable to its enhancement of antioxidant defense activities and regulation of Cd uptake, transport, and distribution in plant organs (Belkadhi et al 2013;Guo et al 2009;Wang et al 2011).…”
mentioning
confidence: 99%